Conceptualizing the ‘All You Can Eat’ game to promote healthy eating habits among young children - Yi-Chin Liu, Noreena; Mohd Tuah, Nooralisa; Ying Chen Yi, Darren (Bulletin of Electrical Engineering and Informatics, 2025)
Childhood obesity is a growing concern globally, with unhealthy eating habits being one of the leading causes. In response, researchers and game designers have investigated the use of serious games to encourage healthy eating among young children. Creating successful serious games to encourage children's good eating habits involves thoughtful consideration of elements such as age-appropriate content, game mechanics, and motivator strategies. The aim of this project is to create a serious game design that promotes and supports healthy eating habits in youngsters. This study evaluates children's existing understanding of nutrition by gathering their comments using a serious game as an example. Various gaming elements are recognized, leading to the creation of a board game named "All You Can Eat" (AYCE). The design evaluation process involves conducting questionnaire surveys and gathering feedback from both parents and children. The results will assist future research in creating and bringing to realisation the AYCE game. This research can be extended to a range of health topics beyond healthy eating habits, such as serious games for learning about cultures and ethics. Researchers, educators, and game designers collaborate to produce unique and interesting games aimed at promoting good eating habits and preventing youngsters’ obesity.